Urban organic waste management via anaerobic digestion as a climate mitigation opportunity in cities of global south: A case study of Itahari, Nepal - Subedi, Tek Raj; Pandit, Sameer; Kafle, Uday Raj (Journal of Innovations in Engineering Education, 2026)
Methane from unmanaged urban organic waste is a growing and underused mitigation target in rapidly warming cities of the Global South. This study quantifies the biodegradable municipal solid waste resource in Itahari Sub-Metropolitan City, Nepal, and assesses the technical potential for anaerobic digestion to convert this waste stream into useful energy and fertilizer. Using stratified random sampling across residential, commercial, and institutional generators, total municipal solid waste generation is estimated at 50.5 tons day−1, of which 65.2% (approx. 33 tons day−1) is organic and suitable for digestion. A 30 tons day−1 continuous stirred-tank reactor system operating under mesophilic conditions (35–38 ◦C) with a 25-day hydraulic retention time is evaluated. The system is projected to produce approx. 2,000 m3 day−1 of biogas with 60% methane, enabling approx. 4,177 kWh day−1 of electricity at 35% combined heat and power efficiency, equivalent to the average demand of about 962 households. In addition to reducing landfill dependence, the process produces digestate suitable for nutrient recovery, supporting circular economy objectives. The results highlight anaerobic digestion as a scalable option for urban methane mitigation and renewable energy co-production in low altitude, warm-climate municipalities, and provide an implementable blueprint for secondary cities across Nepal and comparable Global South contexts.